Cumulative non-high-density lipoprotein cholesterol burden and risk of atherosclerotic cardiovascular disease: a prospective community-based study - Guan, Xu-Min; Shi, Hong-Po; Xu, Shuang; Chen, Yue; Zhang, Rong-Feng; Dong, Ying-Xue; Gao, Lian-Jun; Wu, Shou-Ling; Xia, Yun-Long (Frontiers in Cardiovascular Medicine, 2023)
Background: The relationship between cumulative non-high-density lipoprotein cholesterol (non-HDL-C) burden and atherosclerotic cardiovascular disease (ASCVD) remains unclear. Objective: To prospectively examine the association between cumulative non-HDL-C burden and ASCVD risk in the Kailuan cohort of China. Methods: A total of 49679 subjects who were free of ASCVD participated in three consecutive examinations in 2006, 2008 and 2010 were enrolled. Duration and concentration of cumulative exposure to non-HDL-C (cumNon-HDL-C) were respectively used to estimate the extent of cumulative non-HDL-C burden. The participants were divided into four groups according to durations of cumNon-HDL-C (0, 2, 4 and 6 years) and five groups according to the quintiles of cumNon-HDL-C concentration (<10.93, 10.93 to 12.68, 12.69 to 14.32, 14.33 to 16.72 and ≥16.73 mmol/L). Cox regression models were used to analyze the influence of cumulative non-HDL-C burden on ASCVD risk. Results: We identified 1134 incident ASCVD cases during a mean of 4.89 years of follow-up. Multivariable adjusted analysis revealed that compared with no exposure, cumNon-HDL-C duration 2, 4 and 6 years increased ASCVD risk by 26% (HR: 1.26, 95% CI: 1.07-1.47), 56% (HR: 1.56, 95% CI: 1.31-1.86) and 91% (HR: 1.91, 95% CI: 1.59-2.31) respectively; The hazard ratios (HRs) for the fourth and fifth versus lowest quintile of cumNon-HDL-C concentration were 1.25 and 1.72 for ASCVD. Each standard deviation increment in cumNon-HDL-C concentration was associated with a 10% increased risk of ASCVD. Conclusion: Long-term and higher cumNon-HDL-C were all significantly associated with an increased risk of ASCVD independent of single non-HDL-C level.